The optimization of waste transportation systems in Genuk District, Semarang City - Tiva Sisti; Sri Sumiyati; Budi Prasetyo Samadikun (Sustinere: Journal of Environment and Sustainability, 2022)
Genuk District is a residential development area which has a role as a Semarang City's transportation hubs. It is directly adjacent to Demak Regency and the Java Sea. As of the time of writing, Genuk District has a population of 117,174 people with the total of 130.88 m³ waste transported to the landfill each day and the percentage of waste transportation services in the area is 38.53%. The waste transportation average operational time is 0.2 hours exceeding the amount of working time with the number of 17 trips/day. This planning aims to arrange the waste transportation system in Genuk District by taking into account the traffic congestion in order to get the optimal operational time and costs. Arm roll truck vehicle operating costs in the existing conditions in 2020 was IDR 1,347,411,591.00, while in the optimized condition would be IDR 1,341,405,786.37. Meanwhile, dump truck vehicle operating cost in the existing conditions in 2020 was IDR 302,002,441.00, while in the optimized condition would be IDR 278,453,956.22. The operational time for waste transportation should be started at 06.00-15.00. After optimization, the average remaining working hours becomes 2.68 hours per day with a vehicle's speed of 57.11 km/hour. The planning for waste transportation system optimization will reduce the retribution costs by IDR 900.00 and increase the percentage of waste transportation services to 53%.